Long‐term safety and efficacy of second‐generation everolimus‐eluting stents compared to other limus‐eluting stents and bare metal stents in patients with acute coronary syndrome. Issue 7 (5th August 2014) - Omar, Alfazir; Torguson, Rebecca; Kitabata, Hironori; Pendyala, Lakshmana K.; Loh, Joshua P.; Magalhaes, Marco A.; Satler, Lowell F.; Suddath, William O.; Pichard, Augusto D.; Waksman, Ron
<x xml:space="preserve">Abstract</x> Objectives This study aimed to investigate the long‐term safety and efficacy of everolimus‐eluting stents (EES) compared with other limus‐eluting stents and bare metal stents (BMS) in ACS patients. Background There have been concerns about the long‐term safety of drug‐eluting stents in the setting of acute coronary syndrome. Methods The study cohort included 1, 612 patients presenting with acute coronary syndrome who underwent BMS, SES, E‐ZES, or EES implantation. End points included probable or definite stent thrombosis and major adverse cardiovascular events (MACE), defined as a composite of all‐cause death, Q‐wave myocardial infarction, and target lesion revascularization up to 3 years. Results The overall MACE rates were significantly higher for both BMS and SES, but not E‐ZES, when compared with EES (EES vs. BMS: HR 2.68, 95% CI 1.91–3.78, P <0.001; EES vs. SES: HR 1.75, 95% CI 1.24–2.47, P = 0.001 and EES vs. E‐ZES: HR 1.08, 95% CI 0.65–1.77, P = 0.72). Stent thrombosis rates were similar for EES, E‐ZES, and BMS but higher for SES throughout the 3‐year follow‐up (EES vs. BMS: HR 1.02, 95% CI: 0.31–3.35, P = 0.973; EES vs. SES: HR 4.90, 95% CI: 1.75–13.69, P = 0.002 and EES vs. E‐ZES: HR 1.63, 95% CI 0.37–7.31, P = 0.449). Conclusions There was an improvement in the long‐term outcome for MACE with EES when compared to earlier‐generation stents, but this was comparable with the 2nd‐generation E‐ZES. There was no additional risk of early or late stent thrombosis in EES when compared with BMS. © 2014 Wiley Periodicals, Inc.